Методи розвитку здібностей соціального інтелекту в процесі фахової підготовки - Харченко, С. В.; Kharchenko, S. V.; Svitlana Kharchenko (Право і безпека. – 2016. – № 3 (62). – С. 154–159, 2016)
Для повноцінного розвитку соціального інтелекту особистості потрібні певним чином організоване набуття людиною соціального досвіду й інтенсивна практика взаємодій. Метою роботи було узагальнення соціально-психологічних та психолого-педагогічних методів, які впливають на розвиток здібностей соціального інтелекту спеціалістів професій типу «людина – людина». Наведено структуру соціально-психологічного тренінгу, який, на думку автора, є провідним у вдосконаленні здібностей соціального інтелекту в юнацькому віці та дорослої людини.

Social intellect is the basis of social cognition of a personality. For the full development of the individual’s social intellect we need organized acquiring by a person of social experience in a certain way and intensive practice of interactions. The objective of the paper was a synthesis of social and psychological, psychological and pedagogical methods that affect the development of abilities of social intellect of specialists of the professions such as “human being – human being”. The author has provided methods of social intellect offered in the literature at the stage of professional training: personality-oriented approaches, problem situations, modeling, social roles, methods of analysis of the reflection of psychological and pedagogical situations, etc. and recommendations to teachers and psychologists in the sphere of the development social competence and efficiency of social contacts within the youth. The author has outlined the structure of social and psychological training, which can be used to improve components of social intellect of the specialists in a wide range of professions such as “human being – human being”. The author emphasizes on the need to incorporate such components while improving components of social intellect: formation of special knowledge of psychology of functioning of a subject in a group; developing skills to build interpersonal space; expansion of abilities to properly perceive emotional reactions of others and ethically and correctly to use emotional means to impact on them; developing the abilities to properly understand the motives of others and adjust their behavior in order to solve professional tasks more effectively; expansion of abilities to receive and provide the feedback. The author of the paper has indicated possible training exercises and role plays for this training. Features of effective feedback in the communication process have been provided. The author emphasizes on the feasibility of implementing social and psychological training in the process of professional training of specialists of the professions of “human being – human being”, including the legal professions in order of more effective training for fulfilling professional activities.

Для полноценного развития социального интеллекта личности необходимы определённым образом организованное приобретение человеком социального опыта и интенсивная практика взаимодействий. Целью работы было обобщение социально-психологических и психолого-педагогических методов, влияющих на развитие способностей социального интеллекта специалистов профессий типа «человек – человек». Приведена структура социально-психологического тренинга, который, по мнению автора, является ведущим в совершенствовании способностей социального интеллекта в юношеском возрасте и взрослого человека.
Methods of developing abilities of the social intellect in the process of professional training
Методы развития способностей социального интеллекта в процессе профессиональной подготовки
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; соціальний інтелект; спілкування; методи розвитку соціального інтелекту; соціально-психологічний тренінг; social intellect; communication; methods of development of social intellect; social and psychological training; социальный интеллект; общение; методы развития социального интеллекта; социально-психологический тренинг